Pengaruh Praktik Industri Terhadap Hard Skill Siswa SMK pada Program Keahlian Teknik Pemesinan - Yudha Dwi Prasetyo; Tiwan Tiwan; Arianto Leman Soemowidagdo (Department of Mechanical Engineering Education, 2018)
The implementation of industrial practices is expected to improve skills, verbal abilities, and can provide creative ideas for students in developing skills that have been raised to create the right innovation. This research aims to determine the implementation of industrial attachment for the students of machining study program, and the influence of industrial attachment on the students' hard skill. This research used ex-post facto method with a quantitative approach. The subjects were class XII students of machining study program with a total sample of 98 students. Data were collected using questionnaire and documentation. Data were analyzed using Pearson's product moment correlation and simple regression analysis. Results show that the implementation of industrial attachment for students of machining study program is categorized as